Próba spojrzenia na wymiar społeczny Jasnogórskich Ślubów Narodu w kontekście epoki - Sutowicz, Piotr (Społeczeństwo, 2022)
The taking of the Jasna Góra Vows by a group of almost one million believers on 26 August 1956 within the pastures of Jasna Góra was a ground-breaking event in the post-war history of Poland. It seems that due to our modern historiography, which suffers from excessive secularity, the said event is mentioned only in journalism and sometimes in solely Catholic historiography, with occasional, partial references in the so-called secular public opinion. The very act of Jasna Góra Vows can be considered as purely religious, which will be generally an unfair opinion, or as a manifest of strength of the Polish Church that had survived intensive Stalinization, or finally as the sign of social support for the imprisoned Primate Stefan Wyszyński and a proof that there was no social approval for such a state of affairs.